2020
DOI: 10.1177/1756286420907803
|View full text |Cite
|
Sign up to set email alerts
|

Experiences from treating seven adult 5q spinal muscular atrophy patients with Nusinersen

Abstract: Background: The antisense oligonucleotide Nusinersen recently became the first approved drug against spinal muscular atrophy (SMA). It was approved for all ages, albeit the clinical trials were conducted exclusively on children. Hence, clinical data on adults being treated with Nusinersen is scarce. In this case series, we report on drug application, organizational demands, and preliminary effects during the first 10 months of treatment with Nusinersen in seven adult patients. Methods: All patients received in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 21 publications
2
37
1
1
Order By: Relevance
“…Recent studies have demonstrated the role of DTI in the detection and quantification of muscle fibers fat replacement [ 20 , Table 1 ]; FA is a parameter used to quantify the directional orientation of water molecules within the fibers; FA values are ranged between 0 and 1: in principle, when [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ] tissues are intact, water is forced to move in a specific direction and the FA value is close to 1; unexpectedly patients with severe fat replacement show positive correlation with FA values and negative correlation with Apparent Diffusion Coefficient (ADC); a possible explanation is the artificial increase of FA values in patients with more than 40–45% fat muscle infiltration [ 25 ]. In our cases DTI showed that nusinersen treatment may have a positive effect on size, length and organization of fiber tracts raising the potential neurogenic rescue even in long-standing chronic SMA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have demonstrated the role of DTI in the detection and quantification of muscle fibers fat replacement [ 20 , Table 1 ]; FA is a parameter used to quantify the directional orientation of water molecules within the fibers; FA values are ranged between 0 and 1: in principle, when [ [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] ] tissues are intact, water is forced to move in a specific direction and the FA value is close to 1; unexpectedly patients with severe fat replacement show positive correlation with FA values and negative correlation with Apparent Diffusion Coefficient (ADC); a possible explanation is the artificial increase of FA values in patients with more than 40–45% fat muscle infiltration [ 25 ]. In our cases DTI showed that nusinersen treatment may have a positive effect on size, length and organization of fiber tracts raising the potential neurogenic rescue even in long-standing chronic SMA patients.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal Muscular Atrophy (SMA) is an autosomal-recessive disorder caused by mutations in SMN1 gene, leading to degeneration of alpha motor neurons in the spinal cord resulting in progressive muscle weakness and disability [ [1] , [2] , [3] ]. The results from the pivotal [ 4 ] and more recent trials [ 5 ] with intrathecal nusinersen treatment, as well as the results from real world data [ 6 ], have created great expectations in older patients having long-lasting muscular atrophy and weakness; in fact there is growing evidence that treatment is at the very least stabilizing or providing some degree of improvement in motor function [ 7 ]. However, there are still some critical issues in understanding results in adults, including the lack of natural history data and outcome measures to monitor disease progression [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nusinersen is administered via intrathecal injection, directly into the cerebrospinal fluid (CSF), in a two-phase treatment: (1) a loading phase of four doses 14, 14, and 30 days apart followed by (2) a maintenance phase with a dose every four months. Treatment with Nusinersen showed very promising results in young type 1 patients [ 14 , 15 ] and some positive effects in type 2 and 3 patients (no type 4 patients have been enrolled in clinical trials to date) [ 18 , 19 , 20 ]. Unexpectedly, the latter studies which include adult SMA patients (>18 years old) showed that their response to Nusinersen, evaluated as motor function improvement, was highly variable, with 40–50% of responders at best [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is, therefore, important to gather more information on the natural history of SMA type III for the interpretation of the realworld data that are increasingly becoming available. [19][20][21][22] The aim of this study was to describe the natural history in a large cohort of patients with SMA type III assessed longitudinally using the Hammersmith Functional Motor Scale Expanded (HFMSE). 23 More specifically, we were interested in establishing the distribution of scores at different ages, and the possible patterns of progression in patients with SMA types IIIA and IIIB.…”
mentioning
confidence: 99%